Identification of two major types of age-associated CD8 clonal expansions with highly divergent properties - Clambey, Eric T. (National Academy of Sciences, 2008)
CD8 memory T cells are tightly regulated in young, healthy individuals but are often perturbed in aged animals by the appearance of large CD8 T cell clones. These clones are associated with impaired immunity in the aged. The molecular basis of this phenomenon remains unclear. Here, it is shown that the issue is confused by the fact that the clones are heterogeneous. Some clones bear high, and others, low levels of integrin α(4) (itgα4). These subtypes differ by multiple criteria. They appear in mice of different ages, concentrate in different tissues, and have different stabilities in vivo and responses to stimulation in vitro. itgα4(high), but not itgα4(low), CD8 clonal expansions have several characteristics consistent with a chronically stimulated phenotype. These properties include lowered levels of CD8, decreased expression of some cytokine receptors, and elevated expression of various inhibitory receptors, including the programmed death-1 (PD1) receptor and the killer cell lectin-like receptor G1 (KLRG1). The characteristics of itgα4(high) clonal expansions suggest that they may arise from age-dependent alterations in antigen expression and tolerance. These data redefine CD8 clonal expansions into at least two distinct entities and indicate that there are multiple mechanisms that drive age-related alterations of CD8 T cell homeostasis.